Expect the unexpected? Challenges of prospectively exploring stakeholder engagement in research - Alison O’Shea (Humanities & Social Sciences Communications, 2021)
Abstract Stakeholder engagement in research is increasingly viewed as making a major contribution to assisting impact. This paper draws on a longitudinal, prospective impact study exploring stakeholder engagement in a 3-year tobacco control research project which used stakeholder engagement in the development, testing and dissemination of its return on investment tool. The paper presents the challenges of data collection when undertaking prospective research on stakeholder engagement in health-related research. The impact study used mixed methods of data collection to explore stakeholder engagement in the target project, comprising surveys, interviews and observations of meetings and events involving stakeholders. Stakeholder engagement that actually occurred in the target project, and the data collection methods of stakeholder engagement that were actually used in the impact study, varied substantially from those intended in each case. Data collection for the impact study was dependent on the target project’s stakeholder engagement, which became substantially reduced. Modifications to data collection for the impact study were required. One of the reasons for the reduction of stakeholder engagement was linked to constraints on the target project to meet non-negotiable deadlines. Another factor was concerns about overburdening stakeholders. The knock-on effect of reduced stakeholder engagement highlighted the impact study’s lack of control over its data collection, which was related to the prospective nature of the study. The authors acknowledge that an advantage of a retrospective approach over a prospective one is researchers knowing about data availability and accessibility from the outset. However, the prospective approach of the impact study enabled insight into stakeholder engagement in real-time: how and when it occurred, the challenges, and the experiences of stakeholders and the target project researchers. While the quantity of data gathered was considerably less than anticipated, the quality of data was rich and enabled the impact study objectives to be achieved. With increasing emphasis on public engagement in research and calls for engagement to be evaluated for impact, this paper aims—by highlighting the challenges the impact study experienced—to provide some insight to future research that seeks to respond to those calls.